1995
DOI: 10.1093/carcin/16.8.1783
|View full text |Cite
|
Sign up to set email alerts
|

Exercise intensity dependent inhibition of 1-methyl-l-nitrosourea induced mammary carcinogenesis in female F-344 rats

Abstract: The objective of this experiment was to evaluate the effects of treadmill exercise on tumor induction in an experimental model for breast cancer. Female F-344 rats were injected i.p. with 50 mg MNU/kg body wt at 50 and 57 days of age. Animals were assigned to one of five groups: sham exercise or 35% or 70% maximal treadmill running intensity for 20 or 40 min/day, 5 days per week. These work rates represent an exercise intensity level generally considered insufficient to improve cardiovascular fitness (35% maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 0 publications
3
38
0
1
Order By: Relevance
“…As a result, we can only speculate that body composition was not different between the groups as tumor burden increased. In support of our findings, several other investigations have also shown benefits of physical activity on breast cancer independent of changes in body composition (5,9,10). Therefore, additional hypotheses explaining the changes induced by voluntary wheel running may include alterations in energy sensing pathways, growth related proteins and/or myokines and cytokines (14,15,31).…”
Section: Discussionsupporting
confidence: 92%
“…As a result, we can only speculate that body composition was not different between the groups as tumor burden increased. In support of our findings, several other investigations have also shown benefits of physical activity on breast cancer independent of changes in body composition (5,9,10). Therefore, additional hypotheses explaining the changes induced by voluntary wheel running may include alterations in energy sensing pathways, growth related proteins and/or myokines and cytokines (14,15,31).…”
Section: Discussionsupporting
confidence: 92%
“…The association of physical activity with reduced risk of breast cancer is also supported by several animal studies [28][29][30][31] The studies have shown that both the initiation and promotion/ progression phases of mammary carcinogenesis are inhibited by exercise.…”
Section: Discussionmentioning
confidence: 77%
“…Several prior preclinical reports have shown an inhibitory effect of exercise training on spontaneous and chemically induced tumor growth, metastatic progression and microvessel density without concurrent chemotherapy (4,7,8,26,27). However, almost all of these studies have examined the effects of exhaustive treadmill running at f80% to 90% of maximal oxygen consumption (VO 2max ).…”
Section: Resultsmentioning
confidence: 99%